Pendidikan Keperawatan Berkelanjutan Dan Perencanaan Karir: Strategi Meningkatkan Komunikasi Interprofesional Yang Efektif - Nunung Rachmawati; Luky Dwiantoro; Agus Santoso (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2018)
Interprofessional collaboration will be realized if two or more people from different professions interact to produce a shared understanding that would not have been possible if those professions worked independently. How each profession views the meaning of collaboration must be understood by both parties so that the same perception can be obtained. The application of collaboration between professions is currently limited to traditional or multiprofessional collaboration models. A high level of knowledge is needed by the nursing profession to be able to provide nursing services independently and collaborate with other health workers. This level of education and knowledge gap will hinder the effective communication process among health professionals. Continuous nursing education can be used as a strategy to eliminate the knowledge and education gaps between professions so that it will improve the effective communication process among health professionals. Collaboration is a complex process that requires special attention accompanied by high knowledge in exchanging ideas in discussing patients. Nurses who always try to improve their knowledge and skills to achieve their desired career will have an impact on their ability to exchange ideas (communicate) with other professions or collaborate with other professions. Continuous nursing education and career planning are two strategies that can increase nurses’ knowledge and skills to improve nurses' confidence in exchanging ideas with other professions.